Apoptotic Analysis of Cumulus Cells for the Selection of Competent Oocytes to Be Fertilized by Intracytoplasmic Sperm Injection (ICSI) - Bosco, Liana; Ruvolo, Giovanni; Chiarelli, Roberto; Agnello, Maria; Roccheri, Maria Carmela (Journal of Cells, 2015)
Oocyte quality is one of the main factors for the success of in vitro fertilization protocols. Apoptosis is known to affect oocyte quality and may impair subsequent embryonic development and implantation. The aim of this study was to investigate the apoptosis rate of single and pooled cumulus cells of cumulus cell–oocyte complexes (COCs), as markers of oocyte quality, prior to intracytoplasmatic sperm injection (ICSI).We investigated the apoptosis rate by TUNEL assay (DNA fragmentation) and caspase-3 immunoassay of single and pooled cumulus cells of COCs. The results showed that DNA fragmentation in cumulus cells was remarkably lower in patients who achieved a pregnancy than in those who did not. Cumulus cell apoptosis rate could be a marker for the selection of the best oocytes to be fertilized by intracytoplasmatic sperm injection.